Morfologia e topografia do baço da paca (Cuniculus paca Linnaeus, 1766) - Ribeiro, Isabella F. [UNESP]; Leal, Leonardo M.; de Oliveira, Fabrício S. [UNESP]; Simões, Luciana S.; Moraes, Paola C. [UNESP]; Miglino, Maria A.; Machado, Márcia R.F. [UNESP]; Sasahara, Tais H.C. [UNESP] (FapUNIFESP (SciELO), 2017)
Paca is a large rodent, distributed in part of the Brazilian territory and in Latin America, whose importance is related to the crescent commercial production of exotic meat and in scientific research as a promising experimental model. The morphology and topography of the spleen of paca (Cuniculus paca) is described. Five adult pacas, male and female, were fixed with formaldehyde 10% and stored in 30% saline solution for preservation. The spleen of paca has the anatomical position related to stomach, liver, left kidney, pancreas and greater omentum. The spleenis irregular, longer than larger, with reddish-dark color and smooth texture. Related to the histological description, the spleen has capsule of dense connective tissue that emitted trabeculae projecting into the parenchyma. The capsule and trabeculae has smooth muscle fibers. The parenchyma is composed by the white and red pulp, the latter composed with sinusoids and splenic cords.
Morphology and topography of the spleen of paca (Cuniculus paca)
Keywords: Anatomy; Cuniculus paca; Histology; Lymphoid organ; Paca; Rodent; Wild animal